Moderate Exercise Enhances the Production of Interferon-γ and Interleukin-12 in Peripheral Blood Mononuclear Cells - Zamani, Alireza; Salehi, Iraj; Alahgholi-Hajibehzad, Mahdi (Immune network, 2017)
The purpose of this study was to explore the effect of two months moderate exercise on levels of IFN-γ, IL-12, IL-6 and IL-4 in serum and supernatants of in vitro mitogen-activated (PHA for 48 h) whole blood (WB) and peripheral blood mononuclear cells (PBMCs). Sixteen healthy males participated in running program (30 min/day, 5 days/week). Blood samples were collected in three stages; 24 h before to start exercise, 48 h and two months after the last session of the exercise. The samples were analyzed for the cytokines by ELISA. The levels of IFN-γ and IL-12 were increased significantly in activated PBMCs culture after exercise and were back to normal level after two months rest. A significant elevation of IFN-γ/IL-4 ratio was observed in activated PBMCs culture by acting possibly on IFN-γ. The results suggest that short moderate intensity exercise enhances Th1 immune inflammatory and anti-allergic conditions in response to mitogen.